Characterization of the Proximate Composition, Lipid Oxidation Status, and Mineral Content of Mature Tree Nuts from Nine Hazelnut Cultivars Grown in the United States - Andrew P. Breksa; Ana M. Vilches; Pei-Shih Liang; Natsuko Toyofuku; Ronald P. Haff (Journal of Food Quality)
Hazelnuts are the most popular tree nuts in the world, and regions adjacent the Black and Mediterranean seas are the historic production centers. Characterization of hazelnut cultivars grown in these regions is well reported but is lacking for cultivars grown in the United States. The aim of our study was to characterize nine cultivars selected from the USDA National Germplasm Collection for their proximate composition, lipid oxidation status, and minerals, as well as by NIR spectroscopy. Except for ash content, proximate composition varied across the cultivars and lipids were the predominant component. NIR spectra were similar in pattern and differences in intensity could be accounted for by differences in proximate composition, including lipid, moisture, and protein. Cultivars with the highest moisture content and water activity levels were also those with highest levels of lipid oxidation. Carbon and sulfur content on a fresh weight basis varied from 44.82 g/100 g to 63.82 g/100 g and 96.56 mg/100 g to 164.79 mg/100 g, respectively. The K, P, Ca, Mg, Cu, Fe, Mn, Zn, and B contents were determined by MP-AES. Potassium followed by phosphorus was the most abundant elements. Hazelnuts appear to be a good source of dietary copper and manganese providing up 60.5% and 60.4%, respectively, of the recommended daily value while contributing no more than 0.03% of the daily value for sodium. Characterization results were in ranges like those reported for hazelnuts from Asian and European growing regions. However, each cultivar possessed a unique profile.